THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND SELF-EFFICACY TOWARDS ORGANIZATIONAL CITIZENSHIP BEHAVIOR EMPLOYEES AT SINTESA PENINSULA MANADO HOTEL - Sondakh, Tiffany; Tumbuan, Willem J. F. A.; Saerang, Regina T. (Universitas Sam Ratulangi, 2024)
Organizational Citizenship Behavior (OCB), often an additional role, refers to how employees behave while carrying out company-provided tasks. This behavior is non-binding, voluntary, and unrelated to the formal reward system provided by the company. OCB has the potential to improve organizational efficiency. Therefore, this study aims to analyze the Influence of Perceived Organizational Support and Self-efficacy on Organizational Citizenship Behavior (OCB) among Sintesa Peninsula Manado Hotel employees. the research method used is quantitative. data collection was carried out through a questionnaire distributed to 43 hotel employees. the results of this study show that perceived organizational support has a positive and significant influence on OCB. Then, self-efficacy also has a positive and significant influence on OCB. In addition, perceived organizational support and self-efficacy have a significant influence on Organizational Citizenship Behavior, meaning that Perceived Organizational Support and Self-efficacy of employees, together (simultaneously) can influence the Organizational Citizenship Behavior of Sintesa Peninsula Keywords: Organizational Citizenship Behavior, Perceived Organizational Support, Self-Efficacy